Tracking sustainability in crop pest management in the United States using an eco-efficiency index - Love, Madison; Magarey, Roger D.; Holderman, Brian L.; Carley, Danesha Seth; Maggi, Federico; Singer, Naomi (Frontiers in Insect Science, 2025)
While agricultural pesticides are considered essential for global food security, their use poses significant environmental and human health risks. Integrated Pest Management (IPM) offers a science-based framework to minimize these risks by integrating multiple pest management strategies. However, IPM adoption and funding in the United States have been limited, partly due to a 2001 government report highlighting the lack of measurable reductions in pesticide use. To address this challenge, we propose an index based on eco-efficiency, the ratio of agricultural productivity to environmental impacts, to quantify, track, and incentivize IPM adoption. Using crop production and pesticide use data, including both the mass and toxicity of active ingredients, eco-efficiency scores were calculated for ten major U.S. crop groups from 1992 to 2018. The results demonstrate the potential of this index to monitor progress over time and identify shifts in pesticide use relative to crop production. This approach offers a practical, data-driven tool to evaluate pesticide risk reduction, prioritize IPM research and Extension efforts, and support future policy and funding decisions aimed at promoting more sustainable agricultural practices.